The Attitude and Knowledge of Mothers Regarding Use of Colostrum in Newborn Feeding (Medical Forum Monthly, 2024)
Objective: To assess awareness about the knowledge, attitude and behaviour of mothers about the use of colostrum for the newborn feeding.Study Design: Observational / descriptive /cross-sectional studyPlace and Duration of Study: This study was conducted at Pediatric Outpatient Department, Civil Hospital Bahawalpur from July 10, 2015 to August 8, 2015.Materials and Methods: This study was conducted on mothers who attended Pediatric Outpatient Department, Civil Hospital Bahawalpur for the medical checkup of their children less than one year of age. The mothers were interviewed by the one of the researchers using a structured questionnaire about colostrum including the demographic data. Results: There were 100 mothers included in this study. There were 4% mothers younger than 20 years, 63% in the age group 21-30 years, 20% age group 31-40 years while 3% were older than 40 years. 17% mothers were having at least matriculation, 59% were having education less than that while 34% were uneducated. 94% mothers were house wives. There were 79% mothers who had heard about colostrum; among which 51% heard from either family members or from friends, 21% from medical personnels, 7% from media while 21% never heard of it. There were only 25% mothers who believed that colostrum was the best first feed of newborn, while 61% mothers believed it is GHUTTI that was best. There were 22% mothers who believed that it was beneficial for the health, 13% were in the opinion that it is injurious for the health while 65% replied 'do not know'. There were 41% mothers who told colostrum as yellow and thick, 11% replied it was milk like. There were 32% mothers who believed that colostrum is sufficient for initial newborn feeding, 25% believed it is insufficient. There were only 19% mothers who believed that baby must be put on breast for feeding within half an hour.Conclusion: The awareness of mothers about the use colostrum is poor to moderate.